Development of latex modified concrete from virgin latex paints (2017)
This study investigated the prospects of utilizing virgin latex paints to produce a high performing concrete. Latex variations of 5, 10 and 15% weight of cement were used to produce samples of the concrete. Physical, mechanical, thermal and microstructural analyses were determined. An improved physical property with low moisture penetration and density were observed for the latex modified concrete. Thermal performance showed that the thermal conductivity ranged from 89.12 – 109.37